Deciding to Cross: Norms and Economics of Unauthorized Migration. (August 2013) - Ryo, Emily
Why are there so many unauthorized migrants in the United States? Using unique survey data collected in Mexico through the Mexican Migration Project, I develop and test a new decision-making model of unauthorized labor migration. The new model considers the economic motivations of prospective migrants, as well as their beliefs, attitudes, and social norms regarding U.S. immigration law and legal authorities. My findings show that perceptions of certainty of apprehension and severity of punishment are not significant determinants of the intent to migrate illegally; however, perceptions of availability of Mexican jobs and the dangers of border crossing are significant determinants of these intentions. In addition, individuals' general legal attitudes, morality about violating U.S. immigration law, views about the legitimacy of U.S. authority, and norms about border crossing are significant determinants of the intent to migrate illegally. Perceptions of procedural justice are significantly related to beliefs in the legitimacy of U.S. authority, suggesting that, all else being equal, procedural fairness may produce greater deference to U.S. immigration law. Together, the results show that the decision to migrate illegally cannot be fully understood without considering an individual's underlying values and norms.